末期口腔癌皮膚転移症例に対する Mohs paste の使用経験 - 児玉, 泰光; 小菅, 健裕; 小玉, 直樹; 谷口, 裕重; 田中, 英一郎; 高木, 律男 (日本口腔外科学会雑誌, 2011)
We report the application of Mohs paste as a palliative treatment for a patient with facial and cervical skin metastatic carcinoma arising from uncontrolled oral cancer. An 86-year-old man was referred to our hospital because of tenderness around the left molar region of the mandible. Squamous cell carcinoma of the left buccal mucosa with cervical lymph node metastasis （T2N2bM0） was diagnosed. We performed resection of the oral carcinoma with upper neck dissection. Four months after operation, metastatic masses on the facial and cervical skin appeared. We selected the palliative care because treatments such as surgical resection, adjuvant chemotherapy, and irradiation were contraindicated by advanced age, renal failure, and cerebrovascular disease. The metastatic skin lesion gradually became bigger; therefore we applied Mohs paste to control repeated bleeding and a malodorous discharge from the skin lesion. Bleeding and the malodorous discharge were controlled immediately after spreading the paste on the lesion, and the skin lesion was remarkably shrank day by day. Clinical application of Mohs paste for patients with skin metastatic lesions from oral cancer is a useful procedure for palliative care to improve their quality of life at terminal stage.